The Growth of Government and the Reform of the State in Industrial Countries - Schuknecht, Ludger; Tanzi, Vito. (Washington, D.C. : International Monetary Fund, 1995)
This paper describes the growth of public spending in industrial countries over the past century. It identifies several periods: the periods between 1870 and 1913; the period between the two World Wars; the post World War II period up to 1960; and the period after 1960. Public spending started growing during World War I but its growth accelerated after 1960. The paper outlines the reasons for this growth and speculates that recent government growth has not brought about much economic or social progress. The paper sees the future of government mainly in setting the 'rules of the game,' and provides a rough blueprint for reform. It also discusses experiences with government reform in selected count les, and predicts that over the next decades, public spending as a share of GDP will fall.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet